Menyama Braya Image of Acculturation of Hinduism and Islam in Budakeling Village - I Dewa Gede Yoga; Aris Arif Mundayat; Yuyun Sunesti (Austronesia Akademika, 2024)
This study explores the process of acculturation and tolerance between the Hindu and Muslim communities in Budakeling Village, Bali, focusing on the concept of